Methode zur Analyse und Bewertung von stufenlosen Traktorgetrieben mit mehreren Schnittstellen - Reick, Benedikt (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2018)
The study at hands presents a method for the calculation and evaluation of continuously variable tractor transmissions with multiple interfaces and a various mix out of mechanic, electric and hydraulic technologies. The study concentrates on the correct efficiency calculation of mechanical components as well as the resulting costs of production. The relation of effort and use for each exemplary analyzed concept is shown and explained.